A Challenging Case Of Intravascular Large B-cell Lymphoma Presenting As Pyrexia Of Unknown Origin - Prof. Madya Dr. Asral Wirda Binti Ahmad Asnawi; Alina Md Fauzi; Wilfred, Gilbert; Shukri, Hamizah; Lau, Ngee Siang; Tan, Sen Mui (Philadelphia PA: Wolters Kluwer Health Inc., [2020, 2024)
Indexed by ERA